2019
DOI: 10.1101/599241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of Microglial Activation with White Matter Changes in Dementia with Lewy Bodies

Abstract: Dementia with Lewy bodies (DLB) is the second-leading degenerative dementia afterAlzheimer's disase. Neuropathologically, it is characterized by alpha-synuclein protein deposition with variable degree of concurrent Alzheimer pathology. Neuroinflammation is increasingly recognized as a significant contributor of degeneration. Objective: to examine the relationship between microglial activation as measured with [ 11 C]-PK11195 brain PET and MR diffusion tensor imaging (DTI) in DLB. Methods: nineteen clinically p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The most prominent changes were seen in the corona radiata, corpus callosum, superior longitudinal fasciculus, sagittal stratum and internal capsule. This is in keeping with some previous region of interest studies [30,31] though others have not found changes in these areas [32]. Previous region of interest studies have also reported decreased FA in regions including the uncinate and inferior occipitofrontal fasciculi in DLB compared with controls [5,32,33].…”
Section: Discussionsupporting
confidence: 91%
“…The most prominent changes were seen in the corona radiata, corpus callosum, superior longitudinal fasciculus, sagittal stratum and internal capsule. This is in keeping with some previous region of interest studies [30,31] though others have not found changes in these areas [32]. Previous region of interest studies have also reported decreased FA in regions including the uncinate and inferior occipitofrontal fasciculi in DLB compared with controls [5,32,33].…”
Section: Discussionsupporting
confidence: 91%